THE EFFECT OF TUI NA MASSAGE ON INCREASING APPETITE IN TODDLERS AT AMI MEDIKA CLINIC, SUKABUMI DISTRICT - Reni Anggraeni; Tukimin Bin Sansuwito; Nisha Nambiar; Nenden Lesmana Wati (Proceedings of the 1st International Conference on Social Science (ICSS), 2022)
The nutritional status during infancy needs serious attention from parents, because malnutrition at this time will cause irreversible or irreversible damage. Most parents overcome their child's eating difficulties by giving multivitamins without paying attention to the cause. Today it has been popularized again from the baby massage technique, namely the Tui Na massage.Objective: To determine the effect of Tui Na Massage on increasing appetite in toddlers at the Ami Medika Clinic, Sukabumi Regency. Methods: This study used a quasi-experimental research design with pretest and posttest nonequivalent without control group design. The sample of this study were 35 toddlers who had Tui Na massage therapy at the Ami Medika Sukabumi Clinic. Data analysis used paired t-tests. Results: The mean results before the Tui Na massage was carried out at the Ami Medika Clinic Toddler in Sukabumi Regency obtained a mean result of 17.32. The average results after Tuina massage was carried out on toddlers at the Ami Medika Clinic, Sukabumi Regency, obtained a mean value of 19.06. There is an effect of Tui Na massage on increasing appetite in toddlers at the Ami Medika Clinic, Sukabumi Regency with a value <0.05 p-value = 0.0001. Conclusion: There is an effect of Tui Na Massage on increasing appetite in toddlers at the Ami Medika Clinic, Sukabumi Regency.